7x-3=x+7

Simple and best practice solution for 7x-3=x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3=x+7 equation:


Simplifying
7x + -3 = x + 7

Reorder the terms:
-3 + 7x = x + 7

Reorder the terms:
-3 + 7x = 7 + x

Solving
-3 + 7x = 7 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-3 + 7x + -1x = 7 + x + -1x

Combine like terms: 7x + -1x = 6x
-3 + 6x = 7 + x + -1x

Combine like terms: x + -1x = 0
-3 + 6x = 7 + 0
-3 + 6x = 7

Add '3' to each side of the equation.
-3 + 3 + 6x = 7 + 3

Combine like terms: -3 + 3 = 0
0 + 6x = 7 + 3
6x = 7 + 3

Combine like terms: 7 + 3 = 10
6x = 10

Divide each side by '6'.
x = 1.666666667

Simplifying
x = 1.666666667

See similar equations:

| 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 | | 8g-7=-39 | | 3y+2f-f+1-3y+7=32 | | 2k+5=3 | | -5n+3=-4n-4 | | -6=-6w+4(w+3) | | 4b^2-169y^2= | | 9x+3x=10101010101001101 | | c+bc-11c-4=13c+4-2 | | 2k+10=k+15 | | (8/t-7)-3/t |

Equations solver categories